Letter (copy) : Santiago Gallut Calvo - Tewson, Vincent
1939-07-12 038-0088-001 International HVT/AEC/RC/1340 12th July, 1939. Dr. Betty Morgan, Organising Secretary, Basque Children's Committee, 30, Eccleston Street, S.W.1 Dear Dr. Morgan, RE SANTIAGO GALLUT CALVO. With reference to the telephone conversation you had with this office yesterday, I am enclosing a translation of a letter which we have received from the above refugee in France. I really think that the Committee might take the responsibility for enquiring into the position at the school and taking the child into one of our Homes as a temporary measure. I should be greatly obliged if you could treat this as an urgent matter. The letters from the Nantua (Ain) Furnishing Trades' Union and the Nantua Socialist Party are chiefly a repetition of Mr. Gallut's own statements. I don't think it is necessary to send you translations of them. I have this morning received from the Ain Trades Council Federation a letter reiterating the previous appeal and informing me that permission has been secured from the Prefecture of Police for the Department for the repatriation to Nantua of the child if necessary. Yours sincerely, Assistant Secretary. letter. 292/946/38/88(I)